# SAT Math : How to add exponents

## Example Questions

← Previous 1 3

### Example Question #1 : How To Add Exponents

If a2 = 35 and b2 = 52 then a4 + b6 = ?

522

141,833

140,608

150,000

3929

141,833

Explanation:

a4 = a2 * a2  and  b6= b2 * b* b2

Therefore a4 + b6 = 35 * 35 + 52 * 52 * 52 = 1,225 + 140,608 = 141,833

### Example Question #2 : How To Add Exponents

If 9(x + 5) + 32(x + 5) = 162, what is the value of x?

-3

1

-1

0

3

-3

Explanation:

Since we have two x’s in 9(x + 5) + 32(x + 5) we will need to combine the two terms.

For 32(x + 5) this can be rewritten as

(32) (x + 5) = 9 (x + 5)

So we have 9 (x + 5) + 9 (x + 5) = 162.

Or 2 (9 (x + 5)) = 162

Divide this by 2: 9 (x + 5) = 81 = 9 2

Thus x +5 = 2 or x = -3

*Hint: If you are really unsure, you could have plugged in the numbers and found that the first choice worked in the equation.

Solve for x.

2+ 2x+1 = 72

3

5

4

7

6

5

Explanation:

8 + 2x+1 = 72

2x+1 = 64

2x+1 = 26

x + 1 = 6

x = 5

### Example Question #4 : How To Add Exponents

Which of the following is eqivalent to 5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) , where b is a constant?

1

1/5

5

5b–1

0

0

Explanation:

We want to simplify 5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) .

Notice that we can collect the –5(b–1) terms, because they are like terms. There are 5 of them, so that means we can write –5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) as (–5(b–1))5.

To summarize thus far:

5b – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) – 5(b–1) = 5b +(–5(b–1))5

It's important to interpret –5(b–1) as (–1)5(b–1) because the –1 is not raised to the (b – 1) power along with the five. This means we can rewrite the expression as follows:

5b +(–5(b–1))5 = 5b + (–1)(5(b–1))(5) = 5b – (5(b–1))(5)

Notice that 5(b–1) and 5 both have a base of 5. This means we can apply the property of exponents which states that, in general, abac = ab+c. We can rewrite 5 as 51 and then apply this rule.

5b – (5(b–1))(5) = 5b – (5(b–1))(51) = 5b – 5(b–1+1)

Now, we will simplify the exponent b – 1 + 1 and write it as simply b.

5b – 5(b–1+1) = 5b – 5b = 0

### Example Question #5 : Exponential Operations

If, then what does  equal?

Explanation:

### Example Question #6 : Exponential Operations

Simplify.  All exponents must be positive.

Explanation:

Step 1:

Step 2:

### Example Question #7 : Exponents

Simplify.  All exponents must be positive.

Explanation:

Step 1:

Step 2:

Step 3:

### Example Question #7 : Exponential Operations

Answer must be with positive exponents only.

Explanation:

Step 1:

Step 2: The above is equal to

Evaluate:

Explanation:

Simplify: